MOFs (Metal-Organic Frameworks) derived carbon loaded sodium alginate adsorbent as well as preparation method and application thereof
By encapsulating ZIF-67 derived carbon into a dual crosslinking network composed of polyacrylic acid, sodium alginate and Ca2+ ions, magnetic ZIF-67@C-ACPs polymer beads were designed, which solved the problem that MOFs derived carbon was difficult to separate from water under industrial scale and poor stability in an acidic environment, and achieved efficient removal of dimethylhydrazine.
Patent Information
- Application Number
- CN202510038867.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
The existing MOFs-derived carbon is difficult to completely separate from water under industrial scale, and its stability and recyclability in acidic environments are poor, limiting its application in dimethylhydrazine wastewater treatment.
By using ZIF-67 as a template, functionalized porous carbon was synthesized at different pyrolysis temperatures and encapsulated into a dual crosslinking network based on polyacrylic acid, sodium alginate and Ca2+ ions, magnetic ZIF-67@C-ACPs polymer beads were designed to remove metadimethylhydrazine.
The industrial application of MOFs-derived carbon and the complete separation of water are achieved, which improves its stability and recyclability in an acidic environment, and significantly improves the adsorption amount and removal efficiency of methylhydrazine.
Smart Images

Figure CN119869473A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical adsorption, and specifically relates to a MOFs-derived carbon-loaded sodium alginate adsorbent, a preparation method and an application thereof. Background Art
[0002] As a room-temperature fuel that can be stably stored for a long time and can self-ignite when in contact with oxidants, UDMH has been used as a propellant for missiles and rockets and has been widely used worldwide. It is expected that UDMH will continue to be used in the military and aerospace fields in the next 25 to 50 years. However, UDMH has high carcinogenicity, mutagenicity, teratogenicity and embryotoxicity, and has been classified as a Class 2B carcinogen by the International Agency for Research on Cancer. With the increase in the number of launches, UDMH in the water bodies around the launch site has been regarded as a serious environmental burden and urgently needs to be further effectively treated. At present, many methods for removing UDMH have been developed, such as adsorption, electrochemical method, advanced oxidation method and biodegradation method. Among these methods, adsorption is regarded as a competitive technology because of its advantages such as no by-products, low energy consumption, high adsorption efficiency and simple operation. Therefore, the development of practical and cost-effective adsorbents with satisfactory remediation capabilities is of great significance to maintaining the health of launch site personnel and environmental safety.
[0003] Over the past few decades, metal-organic frameworks (MOFs), as a series of porous crystalline materials, have outstanding characteristics such as organic-inorganic hybridization, large specific surface area, high porosity and customizability. MOFs have easily breakable coordination bonds and abundant carbon components, so direct pyrolysis of MOFs is a simple and efficient porous carbon preparation technology. MOFs-derived carbons usually retain similar morphology and pore characteristics to the original MOFs, and are ideal candidates for a variety of applications such as adsorption, catalysis and electrodes. Compared with traditional porous adsorbents (such as lignin and activated carbon) for UDMH adsorption, MOFs-derived carbons show higher adsorption capacity and high recycling performance. However, MOFs-derived carbons are usually synthesized as fine powders with particle sizes in the nanometer / micrometer range, which are difficult to be completely separated from water at an industrial scale, which inevitably limits their reuse. In addition, MOFs-derived carbons have poor stability and recyclability in acidic environments, which also seriously limits their application in UDMH wastewater treatment. Summary of the invention
[0004] In view of the above-mentioned problems, shaping MOFs-derived carbon into application-oriented forms (such as particles, films and foams) is necessary for practical industrial applications. Biopolymer encapsulation has become a promising solution in recent years. The resulting composites not only maintain the original properties and functions of MOFs-derived carbon, but also have additional composite properties. Sodium alginate is a natural polysaccharide that is abundant in marine algae and has the advantages of biocompatibility, degradability, economic feasibility and non-toxicity. Because sodium alginate is rich in carboxyl and hydroxyl groups and has a large number of pores for adsorbate diffusion, it has been widely used in the adsorption of organic pollutants in water.
[0005] Therefore, the present invention proposes a MOFs-derived carbon-loaded sodium alginate adsorbent, a preparation method and an application thereof. Functionalized porous carbon (ZIF-67@CX) was synthesized at different pyrolysis temperatures (400 ℃, 600 ℃ and 800 ℃) using ZIF-67 as a template, and ZIF-67@Cs was encapsulated into a polyacrylic acid, sodium alginate and Ca-based porous carbon. 2+ ions, magnetic ZIF-67@C-ACPs polymer beads were designed to remove unsymmetrical dimethylhydrazine.
[0006] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent, the preparation method comprising the following steps: Step 1: Prepare ZIF-67 derived carbon using Co(NO3)2·6H2O, 2-methylimidazole and sodium formate as raw materials; Step 2: Prepare ZIF-67@C-ACPs using ZIF-67-derived carbon as substrate.
[0007] Further, the preparation process of step 1 is as follows: Step 101: prepare two methanol solutions of equal volumes, wherein Co(NO3)2·6H2O is dissolved in one methanol solution, and 2-methylimidazole and sodium formate are dissolved in the other methanol solution; Step 102: Mix a methanol solution containing Co(NO3)2·6H2O and a methanol solution containing 2-methylimidazole and sodium formate, and slowly stir at room temperature for 24 h to obtain a purple precipitate, and centrifuge, wash, and dry the purple precipitate in sequence to obtain ZIF-67 powder; Step 103: The prepared ZIF-67 powder is pyrolyzed in a nitrogen atmosphere at a constant heating rate, and naturally cooled to room temperature to obtain a black powder, which is named ZIF-67@CX, where X represents the pyrolysis temperature, and the pyrolysis temperatures include 400°C, 600°C, and 800°C.
[0008] Furthermore, in step 101, the volume of the methanol solution is 100 mL, and the mass ratio of Co(NO3)2·6H2O, 2-methylimidazole and sodium formate is: 1.44:1.62:1.34.
[0009] Furthermore, in step 102, methanol washing is used, and the number of washing times is 3 times; the centrifugation method is: centrifugation at a rotation speed of 7000 rpm for 10 min; the drying method is: vacuum drying at 60°C for 12 h.
[0010] Furthermore, in step 103, the heating rate is 5°C / min, the pyrolysis temperature is 800°C, and the pyrolysis time is 2h.
[0011] Furthermore, the preparation process of step 2 is as follows: Step 201: preparing a ZIF-67@C-800 / sodium alginate suspension; Step 202: preparing a solidifying liquid; Step 203: Drop a uniform ZIF-67@C-800 / sodium alginate suspension into a solidifying liquid and harden for 6 h to obtain beads. Collect the beads and wash them three times in a row with ultrapure water. After freeze-drying, spherical ZIF-67@C-ACPs are synthesized.
[0012] Furthermore, the specific preparation process of step 201 is: 2.0 g ZIF-67@C-800 is dispersed in 40 mL sodium alginate aqueous solution, and mechanically stirred at 60 ° C for 30 min to obtain a ZIF-67@C-800 / sodium alginate suspension.
[0013] Furthermore, the specific preparation process of step 202 is: dissolving 5.64 g of CaCl2 in 900 mL of polyacrylic acid aqueous solution to prepare a solidifying liquid.
[0014] In a second aspect, the present invention also protects a MOFs-derived carbon-loaded sodium alginate adsorbent, which is prepared by a method for preparing a MOFs-derived carbon-loaded sodium alginate adsorbent.
[0015] In a third aspect, the present invention also protects the use of a MOFs-derived carbon-loaded sodium alginate adsorbent in removing unsymmetrical dimethylhydrazine from wastewater.
[0016] Beneficial effects: (1) In this paper, functionalized porous carbon (ZIF-67@CX) was synthesized using ZIF-67 as a template at different pyrolysis temperatures (400 °C, 600 °C, and 800 °C), and ZIF-67@CX was encapsulated into a polyacrylic acid, sodium alginate, and Ca-based nanostructured carbon. 2+ions, magnetic ZIF-67@C-ACPs polymer beads were designed. Only H2O was used as solvent in the preparation of polymer beads, the preparation process was simple, and the product was easy to obtain.
[0017] (2) This invention combines ZIF-67 derived carbon / sodium alginate / Ca for the first time 2+ ZIF-67@C-800 and ZIF-67@C-ACPs were used to remove UDMH from simulated wastewater. ZIF-67@C-800 and ZIF-67@C-ACPs removed UDMH from simulated wastewater with extremely high performance, and their maximum adsorption capacities were 644.24 mg / g and 351.96 mg / g, respectively. They can remove UDMH from water with high selectivity, and bring hope for the practical application of MOFs-derived carbon-based recyclable adsorbents in the field of water purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 are the SEM images of ZIF-67@C-ACP and the mapping diagrams of C, O, N, Ca and Co elements; ab are the SEM images of ZIF-67@C-ACP, where a is 500 μm; b is 2 μm; c is the mapping diagram of ZIF-67@C-ACP, and d~h are the mapping diagrams of C, O, N, Ca and Co elements in ZIF-67@C-ACP, respectively.
[0020] Figure 2 This is a digital photo of ZIF-67@C-ACP.
[0021] Figure 3 are the magnetization curves of ZIF-67@C-800 and ZIF-67@C-ACPs (the inset shows the magnetic separation states of ZIF-67@C-800 and ZIF-67@C-ACP).
[0022] Figure 4 It is a comparison chart of the adsorption capacity of different adsorbents.
[0023] Figure 5 The effect of initial pH value on the adsorption capacity and zeta potential of ZIF-67@C-ACPs.
[0024] Figure 6It is the influence of coexisting ions on the adsorption amount of ZIF-67@C-ACPs.
[0025] Figure 7 are the adsorption amount and removal efficiency of ZIF-67@C-ACPs under different regeneration cycles.
[0026] Figure 8 is the Co leaching concentration of ZIF-67@C-ACP at different pH values. DETAILED DESCRIPTION
[0027] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0028] Unless otherwise specified, the test materials used in the following examples were purchased from conventional biochemical reagent stores.
[0029] Material: Sodium alginate (SA, viscosity: )、Calcium chloride anhydrous( ), sodium formate (HCOONa, 98%), polyacrylic acid (PAA, average Mw ~2000) and methanol (CH3OH, 99.9%) were purchased from Adamas Reagent Co., Ltd. Cobalt nitrate hexahydrate ( ) and 2-methylimidazole (98%) were purchased from MacLean Biochemical Technology Co., Ltd. Anhydrous ethanol ( ) and commercial activated carbon (AC, 200 mesh) were purchased from Shanghai Titan Technology Co., Ltd. Potassium chloride (KCl, 99.5%), potassium bicarbonate (KHCO3, 99.5%), magnesium sulfate (MgSO4, 98%), sodium sulfate (Na2SO4, 99%), sodium carbonate (Na2CO3, 99.8%), sodium nitrate (NaNO3, 99%), sodium hydroxide (NaOH, 96%), and hydrochloric acid (HCl, 37%) were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0030] Embodiment 1: This example specifically introduces a preparation process of a MOFs-derived carbon-supported sodium alginate adsorbent, as follows: Step 1: Preparation of ZIF-67 derived carbon; Dissolve 1.44 g Co(NO3)2·6H2O in 100 mL methanol (completely dissolved). Similarly, dissolve 1.62 g 2-methylimidazole and 1.34 g sodium formate in another 100 mL methanol (completely dissolved). 2+The solution was mixed with 2-methylimidazole and stirred slowly at room temperature for 24 h. The purple precipitate was centrifuged (7000 rpm, 10 min) and washed thoroughly three times with methanol, and then dried under vacuum at 60 °C for 12 h.
[0031] The prepared ZIF-67 powder was then pyrolyzed in a tube furnace at a heating rate of 5 °C / min at designated temperatures (400 °C, 600 °C, and 800 °C) in a nitrogen atmosphere for 2 h. After naturally cooling to ambient temperature, black powders were obtained, named ZIF-67@CX (where X represents the pyrolysis temperature, 400 °C, 600 °C, and 800 °C).
[0032] Step 2: Using ZIF-67@C-800 as substrate, prepare ZIF-67@C-ACPs; Typically, 2.0 g of ZIF-67@C-800 was dispersed in 40 mL of sodium alginate aqueous solution (15 mg / mL) and mechanically stirred (1000 rpm) at 60 °C for 30 min. 5.64 g of CaCl2 was dissolved in 900 mL of polyacrylic acid aqueous solution (0.05 mol / L) to prepare the curing solution. Then, the uniform sodium alginate suspension was dropped into the curing solution. After hardening for 6 h, the beads were collected and washed three times in a row with ultrapure water. After a freeze-drying process, spherical ZIF-67@C-ACPs were successfully synthesized.
[0033] Embodiment 2: The ZIF-67@C-ACPs prepared in Example 1 were used as experimental objects to study their energy absorption performance.
[0034] For comparison, activated carbon-ACP polymer beads (AC-ACPs) were synthesized by the same method. Typically, 2.0 g of activated carbon was dispersed in 40 mL of sodium alginate aqueous solution (15 mg / mL) and mechanically stirred (1000 rpm) at 60 °C for 30 min. 5.64 g of CaCl2 was dissolved in 900 mL of polyacrylic acid aqueous solution (0.05 mol / L) to prepare the curing solution. Then, the uniform sodium alginate / activated carbon suspension was dropped into the curing solution. After hardening for 6 h, the beads were collected and washed three times in a row with ultrapure water. After a freeze-drying process, spherical AC-ACP was successfully synthesized.
[0035] 1. Intermittent adsorption experiment: Unsymmetrical dimethyl hydrazine was selected as the target pollutant to study the adsorption characteristics of the synthetic materials. The simulated unsymmetrical dimethyl hydrazine aqueous solution was prepared by diluting the unsymmetrical dimethyl hydrazine stock solution ( ). Unless otherwise stated, all experiments were performed in 100 mL conical flasks using 50 mL of 50 mg / L UDMH solution, and the pH was kept around 8.4 without adjustment. Subsequently, 30 mg of adsorbent was added and the mixture was shaken in a thermostatic air bath shaker at 100 rpm at 298 K. A series of single-factor experiments were performed to study the effects of dosage (0.2–1.0 g / L), initial concentration (25–500 mg / L), adsorption temperature (278 K, 288 K, and 298 K), and pH (3–11). The initial pH of the UDMH solution was adjusted with 0.1 mol / L HCl or 0.1 mol / L NaOH solution. In the cyclic regeneration experiments, the used ZIF-67@C-ACPs were magnetically separated after adsorption and eluted multiple times with ethanol and ultrapure water. Then, the material was freeze-dried under vacuum and directly used for the next adsorption–desorption cycle.
[0036] 2. Results and discussion 2.1 Characterization of adsorption column: In order to obtain detailed information on the distribution of ZIF-67@C-800 in ZIF-67@C-ACPs, we split a bead into two and characterized the morphology of one of the pieces by SEM ( Figure 1 a and Figure 1 (b) The elemental map image shows that the distribution of C, O, N, Ca and Co elements is relatively uniform (e.g. Figure 1 The d in Figure 1 h), indicating that ZIF-67@C-800 is uniformly dispersed throughout the ZIF-67@C-ACP ( Figure 1 In addition, ZIF-67@C-ACPs can be conveniently synthesized under continuous flow conditions to produce uniform beads with a diameter of approximately 4.3 mm ( Figure 2 ).
[0037] The magnetic properties of the synthesized adsorbent were studied by VSM. Figure 3 The saturation magnetizations of ZIF-67@C-800 and ZIF-67@C-ACPs were 45.7 emu / g and 30.5 emu / g, respectively, indicating that they have high magnetic properties and can be quickly recovered from the suspension by magnetic separation.
[0038] 2.2 Comparison of different types of adsorbents: The adsorption of UDMH on a series of adsorbents was systematically tested ( Figure 4). The results show that the adsorption amount increases with the increase of pyrolysis temperature, which may be related to the increase of total pore volume, pore size and graphitization degree of the adsorbent. The adsorption amount of ZIF-67@C-ACPs is higher than that of other adsorbents except ZIF-67@C-800 (82.20 mg / g), which indicates that the combination with sodium alginate improves the pore structure and active sites, thereby increasing the adsorption amount. Compared with ZIF-67@C-800, ZIF-67@C-ACPs not only has a comparable adsorption capacity (79.20 mg / g), but also has the advantage of magnetic recyclability. Considering the practical application, ZIF-67@C-ACPs was selected to study the effect of system parameters on adsorption. In contrast, the adsorption amount of ZIF-67@C-ACPs is 1.67 times that of AC-ACPs (47.45 mg / g).
[0039] 2.3 Effect of initial pH value and coexisting ions: In order to analyze the effect of initial pH value, the adsorption performance of ZIF-67@C-ACPs on UDMH in solutions with different pH values and their corresponding Zeta potential values ( Figure 5 ). It is worth emphasizing that ZIF-67@C-ACPs has excellent adsorption performance for UDMH in a wide pH range (3~11) and no obvious changes occur, which indicates that electrostatic interaction is not the main factor in the adsorption process. In order to study the effect of coexisting ions on the adsorption of UDMH, common ions (KCl, KHCO3, MgSO4, Na2SO4, Na2CO3 and NaNO3) with different concentrations were studied. The results showed that the effect of coexisting ions on the adsorption of UDMH is negligible ( Figure 6 ).
[0040] 2.4 Reusability of ZIF-67@C-ACPs: After each cycle, the magnetic ZIF-67@C-ACPs were separated by magnet, and solvent elution was performed using anhydrous ethanol and ultrapure water due to the high solubility of UDMH. The reusability of ZIF-67@C-ACPs for UDMH was studied through effective regeneration and subsequent cycles. Figure 7 ). Due to the formation of strong chemical bonds and irreversible adsorption sites between ZIF-67@C-ACPs and UDMH, the adsorption amount and removal efficiency decreased with the increase of the number of cycles. Therefore, some active sites on ZIF-67@C-ACPs were irreversibly occupied, hindering regeneration and resulting in a slight decrease in adsorption capacity. Interestingly, ZIF-67@C-ACPs were magnetically separable and could still maintain 90.3% of the initial adsorption amount after six cycles, showing its great potential as a durable UDMH fixed adsorbent.
[0041] 3.5 Co leaching concentration: In order to ensure the safety, stability and environmental sustainability of the adsorbent, metal leakage experiments must be conducted. By comparing the metal ion release of ZIF-67@C-800 and ZIF-67@C-ACPs under different pH conditions, it can be directly seen that ZIF-67@C-ACPs has the advantage in stability ( Figure 8 ). Compared with pure ZIF-67@C-800, the Co leaching in ZIF-67@C-ACPs is significantly reduced under acidic conditions. Specifically, at pH 3, the cobalt ion leaching concentration of ZIF-67@C-800 is close to 8 mg / L. As the pH value increases, the concentration decreases rapidly, tends to be close to 1 mg / L around pH 7, and remains stable in a higher pH range (9~11). The cobalt ion leaching concentration of ZIF-67@C-ACPs is significantly lower than that of ZIF-67@C-800 as a whole. At pH 3, the leaching concentration of ZIF-67@C-ACPs is about 2 mg / L; as the pH value increases, the concentration gradually decreases, drops to about 0.5 mg / L at pH 7, and stabilizes at a level close to 0 in a higher pH range. The cobalt ion leaching concentration of ZIF-67@C-ACP is significantly lower than that of ZIF-67@C-800 in the entire pH range, especially under neutral to alkaline conditions (pH ≥ 7), the leaching concentration of ZIF-67@C-ACP is close to 0, showing excellent chemical stability.
[0042] The embodiments described above are only preferred specific implementation modes of the present invention, and the protection scope of the present invention is not limited thereto. Any simple changes or equivalent replacements of the technical solutions that can be obviously obtained by any technician familiar with the field within the technical scope disclosed in the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent, characterized in that: The preparation method comprises the following steps: Step 1: Prepare ZIF-67 derived carbon using Co(NO3)2·6H2O, 2-methylimidazole and sodium formate as raw materials; Step 2: Prepare ZIF-67@C-ACPs using ZIF-67-derived carbon as substrate.
2. The method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent according to claim 1, characterized in that: The preparation process of step 1 is as follows: Step 101: prepare two methanol solutions of equal volumes, wherein Co(NO3)2·6H2O is dissolved in one methanol solution, and 2-methylimidazole and sodium formate are dissolved in the other methanol solution; Step 102: Mix a methanol solution containing Co(NO3)2·6H2O and a methanol solution containing 2-methylimidazole and sodium formate, and slowly stir at room temperature for 24 h to obtain a purple precipitate, and centrifuge, wash, and dry the purple precipitate in sequence to obtain ZIF-67 powder; Step 103: The prepared ZIF-67 powder is pyrolyzed in a nitrogen atmosphere at a constant heating rate, and naturally cooled to room temperature to obtain a black powder, which is named ZIF-67@CX, where X represents the pyrolysis temperature, including 400°C, 600°C and 800°C.
3. According to the method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent according to claim 2, in step 101, the volume of the methanol solution is 100 mL, and the mass ratio of Co(NO3)2·6H2O, 2-methylimidazole and sodium formate is: 1.44:1.62:1.
34.
4. The method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent according to claim 3, characterized in that: In step 102, methanol washing is performed 3 times; the centrifugation method is: centrifugation at a rotation speed of 7000 rpm for 10 minutes; the drying method is: vacuum drying at 60°C for 12 hours.
5. The method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent according to claim 2, characterized in that: In step 103, the heating rate is 5°C / min, the pyrolysis temperature is 800°C, and the pyrolysis time is 2 h.
6. The method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent according to claim 5, characterized in that: The preparation process of step 2 is as follows: Step 201: preparing a ZIF-67@C-800 / sodium alginate suspension; Step 202: preparing a solidifying liquid; Step 203: Drop a uniform ZIF-67@C-800 / sodium alginate suspension into a solidifying liquid and harden for 6 h to obtain beads. Collect the beads and wash them three times in a row with ultrapure water. After freeze-drying, spherical ZIF-67@C-ACPs are synthesized.
7. The method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent according to claim 6, characterized in that: The specific preparation process of step 201 is: disperse 2.0 g ZIF-67@C-800 in 40 mL sodium alginate aqueous solution, and mechanically stir at 60° C. for 30 min to obtain a ZIF-67@C-800 / sodium alginate suspension.
8. The method for preparing a MOFs-derived carbon-supported sodium alginate adsorbent according to claim 6, characterized in that: The specific preparation process of step 202 is: dissolving 5.64 g of CaCl2 in 900 mL of polyacrylic acid aqueous solution to prepare a solidifying liquid.
9. A MOFs-derived carbon-supported sodium alginate adsorbent, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a MOFs-derived carbon-supported sodium alginate adsorbent as claimed in claim 9 in removing unsymmetrical dimethylhydrazine from wastewater.
Citation Information
Cited By
Application of catalyst taking waste manganese adsorbent as raw material in electro-Fenton efficient degradation of antibiotics in water
CN121158899A